2020
DOI: 10.1088/2053-1591/abcba7
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of graphene oxide filler content on the dentin bond integrity, degree of conversion and bond strength of experimental adhesive. A SEM, micro-Raman, FTIR and microtensile study

Abstract: The study aimed to evaluate the effect of graphene oxide (GO) nano-filler content in experimental dental adhesive on its degree of conversion (DC), microtensile bond strength (μTBS) and structural reliability, using Fourier transform infrared spectroscopy (FTIR), Micro-Raman spectroscopy and Scanning electron microscopy (SEM). A resin adhesive was fabricated (control adhesive - CA) and fabricated GO nano-particles were added at 0.5% and 2.0% (m/m) to produce adhesives GOA1 and GOA2 respectively. One hundred an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 28 publications
4
36
0
Order By: Relevance
“…DC of the two adhesive groups was also evaluated in our study, and although the results demonstrated comparable DC for both adhesive groups, still, higher DC values for EA-rGO-0% adhesive were seen compared with rGO-5% adhesive. Earlier, Bin-Shuwaish et al also reported an inverse positive linear relationship between increasing GO content and DC [ 32 ], and our results agree with their findings. Aside from rGO, researchers have also previously incorporated various other inorganic fillers like hydroxyapatite and silica in the adhesive and reported a similar trend (DC decreases linearly with the increasing filler content) [ 27 , 47 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…DC of the two adhesive groups was also evaluated in our study, and although the results demonstrated comparable DC for both adhesive groups, still, higher DC values for EA-rGO-0% adhesive were seen compared with rGO-5% adhesive. Earlier, Bin-Shuwaish et al also reported an inverse positive linear relationship between increasing GO content and DC [ 32 ], and our results agree with their findings. Aside from rGO, researchers have also previously incorporated various other inorganic fillers like hydroxyapatite and silica in the adhesive and reported a similar trend (DC decreases linearly with the increasing filler content) [ 27 , 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…The rGO nanoparticles, when observed on the SEM, revealed flake-shaped morphology, and this finding is consistent with several previous studies [ 25 , 32 ]. In general, the reduction process to yield GO nanoparticles produces flake-shaped sharp-edged sheets due to the presence of oxygen groups in the oxide sheets [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…This loss of bond leads to the formation of nano-gaps resulting in bond failure and development of secondary caries [ 6 ]. To overcome failure of adhesion over time, addition of inorganic fillers in adhesives is promoted to improve dentin interaction of adhesive resins and possibly minimize dentin-adhesive degradation [ 7 ]. Previous studies have shown that addition of fillers in adhesives can reduce water sorption and solubility [ 8 ], in addition to enhancing its mechanical properties [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The polymer/graphene based nanocomposite has been an interesting research area for many years and various polymers have been intermingled with graphene [ 15 , 16 , 17 , 18 , 19 ]. The incorporation of graphene has greatly improved the mechanical properties of the polymers.…”
Section: Introductionmentioning
confidence: 99%